Effects of post-activation potentiation on athletic performance: A mini-review - Jaffe, D.; Hewit, J.; Costantini, T. (COJ Technical & Scientific Research, 2018)
Background and Purpose: Post-Activation Potentiation (PAP) is an increase in the contractile ability of a muscle that is demonstrated subsequent to a maximal or near-maximal bout or exertion [1,2]. The purpose of this investigation was to examine the effects that PAP has on athletic performance. Method: The review included articles from peer-reviewed journals with sufficient data related to the purpose and focus of the study. Inclusion criteria include randomized control trials, systematic reviews and meta-analysis published since 1993. Key words included: "post-activation potentiation", "complex training", "power" and "athletic performance."Results: Twenty relevant studies were identified; various experimental protocols were employed, including both acute and chronic effects of post-activation potentiation on physical performance. All studies were published 1993 through 2015, providing a robust overview of experimentation over the last 25 years.Discussion and Conclusion: Among studies analyzed in this mini-review, the consensus reached regarding the effects of post-activation potentiation on athletic performance was relatively positive. Most studies followed similar data collection strategies, with slight variations in load, rest-interval, and modality of assessment. The majority of these studies demonstrated significant increases in athletic performance in concert with moderate duration recovery intervals. More research is necessary to identify optimal load patterns and recovery intervals for promoting enhanced athletic performance.